Étude Phytochimique et activité antifongique d’extraits de quelques Euphorbiaceae médicinales utilisées chez les Baoulé du District de Yamoussoukro (Côte d’Ivoire) - Isidore, Saraka Allou; Kouabenan, Abo; Kiyinlma, Coulibaly; Noël, Zirihi Guédé (European Scientific Journal, ESJ, 2018)
An ethnobotanical survey was carried out in the District of Yamoussoukro (Central Côte d’Ivoire) in order to evaluate the biocontrol potential against fungal plant pathogens, of Euphorbiaceous plants used as medicines by the native population. Twelve (12) species were collected. The antifungal activity was assessed using the two-fold dilution method on PDA medium with ethanolic and aqueous extract derived from leaves of six plants. Results pointed out that only 70% ethanolic extracts from Alchornea cordifolia (EE13) possess fungicidal properties on both Fusarium sp. and Phytophthora sp. The antifungal activities are more effective with ethanolic extracts than aqueous extracts. With a minimal inhibitory concentration MIC = 25±0.0 mg/ml, a minimal concentration for 50% of inhibition IC50 = 10±0.05 mg/ml and a minimal fungicide concentration MFC = 200±0.0 mg/ml Fusarium sp. appears to be the most sensitive. Phytophthora sp. is less sensitive with a MIC = 50±0.0 mg/ml, an IC50 = 12±0.05 mg/ml and a MFC = 200±0.0 mg/ml. Phytochemical screening revealed the presence of seven major groups of compounds among which saponins and catechin are the most abundant in aqueous extracts. Polyphenols, flavonoids, polyterpenes and sterols as well as tannins are present in both alcoholic and aqueous extracts of Alchornea cordifolia. These compounds could justify its antifungal activity and traditional use.